2011
DOI: 10.5588/ijtld.10.0680
|View full text |Cite
|
Sign up to set email alerts
|

Carotid atherosclerosis in patients with untreated chronic obstructive pulmonary disease

Abstract: In newly diagnosed untreated patients with COPD, the carotid artery IMT and hsCRP were significantly higher than in healthy subjects. These findings suggest that systemic inflammation may play a potential role in preclinical atherosclerosis in COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
22
1
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 0 publications
8
22
1
3
Order By: Relevance
“…Additionally, CIMT was found to be significantly higher among our study COPD patients than the controls (0.85±0.18 mm vs. 0.63±0.076 mm, p<0.001). These results coincide with the results of other studies in the literature (4,17,(33)(34)(35)(36)(37)(38)(39).…”
Section: Discussionsupporting
confidence: 83%
“…Additionally, CIMT was found to be significantly higher among our study COPD patients than the controls (0.85±0.18 mm vs. 0.63±0.076 mm, p<0.001). These results coincide with the results of other studies in the literature (4,17,(33)(34)(35)(36)(37)(38)(39).…”
Section: Discussionsupporting
confidence: 83%
“…We also observed signifi cant univariate relationships for 3 He VDP with carotid artery IMT, TPV and VWV, consistent with previous studies that showed relationships between spirometry measurements and carotid IMT (3,4,6,17,55,56), although this is the fi rst report of such relationships in subjects with normal pulmonary function. Similarly, multivariate regression models that controlled for cardiovascular and pulmonary disease risk factors showed that VDP is a signifi cant predictor of carotid artery IMT, VWV and TPV.…”
Section: Copd Downloaded From Informahealthcarecom By University Of supporting
confidence: 66%
“…Previous work in COPD patients (3,4,6,7,17,55,56) reported a relationship for IMT with FEV 1 and emphysema measurements, but this was not observed here in ex-smokers without COPD. We were likely underpowered to detect diff erences in IMT between subgroups as these previous studies investigating IMT in COPD and healthy older subjects used sample sizes ranging from 305 to 14,480 subjects.…”
Section: Copd Downloaded From Informahealthcarecom By University Of contrasting
confidence: 47%
See 1 more Smart Citation
“…Eickhoff ve arkadaşları çalışmalarında stabil KOAH hastalarında sigara içen veya içmeyen sağlıklı kişilere göre daha yüksek KİMK'ler ölçmüşlerdir (24). Kim ve arkadaşları da yeni tanı alan ve tedavisine başlanmamış KOAH'lı hastalarda sağlıklı bireylere göre KİMK'yi anlamlı yüksek olarak bulmuşlardır (25). Benzer şekilde, van Gestel ve arkadaşları da damar cerrahisi geçiren hastalarda KO-AH'ın KİMK artışıyla ilişkisini ve artmış KİMK'nin artmış kardiyovasküler mortaliteyle ilişkisini belirtmişler-dir (26).…”
Section: Discussionunclassified